TOTAL FACTOR PRODUCTIVITY AND FRONTIER PRODUCTION FUNCTION = PRODUKTIVITAS FAKTOR PRODUKSI TOTAL DAN FUNGSI PERODUKSI FRONTIER - Sri Widodo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1986)
The total factor productivity became an interesting concept in the measurement of productivity growth. Productivity is a ratio of output to input. The most common measurement of productivity is single factor productivity or partial productivity such as of land, labor, or capital.A total (factor) productivity is a productivity of all factors of production where the factors are aggregated. In cross-sectional studies this total productivity is a ratio of actual to potential output where the potential output is estimated from ther frontier production function. One of the methods to estimate this frontier function is by using linear programming technique.The total productivity does not always coincide with a single factor productivity of land (yield), that in the study area the larger farms tend to have higher total productivity than yield